Teachers’ Perceptions, Plans, and Their Practices on Teaching Vocabulary in Context at SMP N 1 Parakan, Temanggung - Ilmi, Istiqomah Khoirul; Wuli Fitriati, Sri (English Education Journal, 2020)
This study is aimed at examining teachers’ perceptions, plans, and practices on teaching vocabulary in context at SMP N 1 Parakan. A case study was employed to describe the phenomena happened in this study. Two teachers were selected to become participants of the study. The data gathered through questionnaire, interview, observations, and document analysis. The result showed that both teachers had good perception on teaching vocabulary. Both teachers perceived that vocabulary became the important aspects in English in enabling the English skills both receptive (listening and reading) and productive (speaking and writing). In planning vocabulary teaching, both teachers planned their teaching by involving some elements of vocabulary material in the lesson plans. Teachers inserted vocabulary material, list of vocabulary, and activities to learn vocabulary. However, teachers did not provide certain strategy applied in the classroom. In the real practices in the classroom, the teachers applied a direct method while teaching vocabulary by providing students a list vocabulary. This direct vocabulary learning built a large recognition of vocabulary for students. Relating to the alignment and misalignment of teachers’ perception, plans and practices on teaching vocabulary, it was revealed that those aspects were aligned proved by teachers had good perception, plans and practices on teaching vocabulary. It was expected for further research to continue this study by adding another subject such as students so that it will give another perspective.